2013
DOI: 10.1002/jsfa.6289
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and molecular detection of toxigenic Aspergillus species in food grain samples from India

Abstract: Since the southern states of India are temperate regions, environmental factors, especially temperature and relative humidity, may be responsible for the high levels of mycotoxins present in the grains studied. Therefore there is a need to generate awareness among farmers and consumers about the possible adverse health effects of high levels of mycotoxins present in different food grains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 30 publications
(25 reference statements)
0
27
0
Order By: Relevance
“…These species were dominant in sorghum from Argentina, Thailand and Brazil (Alves dos Reis et al, 2010;Gonzalez et al, 1997;Pitt et al, 1994). A. carbonarius was not detected in the present study; however, this species showed a higher distribution in Indian sorghum samples (Priyanka et al, 2014).…”
Section: Mycobiota Determinationmentioning
confidence: 62%
See 1 more Smart Citation
“…These species were dominant in sorghum from Argentina, Thailand and Brazil (Alves dos Reis et al, 2010;Gonzalez et al, 1997;Pitt et al, 1994). A. carbonarius was not detected in the present study; however, this species showed a higher distribution in Indian sorghum samples (Priyanka et al, 2014).…”
Section: Mycobiota Determinationmentioning
confidence: 62%
“…Da Silva et al (2006) studied the genetic variability of 21 Fusarium verticilloides strains isolated from sorghum cultivated in the State of São Paulo, Brazil, using SPAR (Single Primer Amplification Reaction) markers while Divakara et al (2013) identified and characterized 27 Fusarium spp., isolated from 58 sorghum seed samples collected across India, sequencing the transcription elongation factor 1 alpha gene and analyzing the Inter Simple Sequence Repeat (ISSR) polymorphisms. Additionally, Priyanka et al (2014) studied the diverse distribution of 200 Aspergillus strains from a total of 320 samples of maize, paddy, sorghum and groundnut by species-specific PCR assays. However, to our knowledge, there are no previous publications about the mycobiota of African sorghum in which molecular methods are used to differentiate taxa.…”
Section: Fungusmentioning
confidence: 99%
“…Unfortunately, no organized effort has yet made to address this issue in India. Only a few reports have been published on mycotoxin contamination of cereals in India . Our previous studies indicated that samples of rice and finger millet were contaminated with toxigenic Fusarium species.…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with the observation that successful colonization postharvest as influenced by storage conditions may influence the growth of mycotoxigenic fungi and the subsequent production of toxins (Chulze, 2010). Priyanka et al (2014) studied the molecular diversity of toxigenic Aspergillus species from food samples grown in highrainfall regions in India where 200 isolates were recovered from 320 grain samples. This study also points to a higher fungal burden in Kenya as compared to India.…”
Section: Discussionmentioning
confidence: 84%